2014
DOI: 10.1155/2014/272586
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Shear Wave Imaging to Assess Arterial Nonlinear Behavior and Anisotropy: Proof of Principle via Ex Vivo Testing of the Horse Aorta

Abstract: Supersonic shear wave imaging (SSI) is a noninvasive, ultrasound-based technique to quantify the mechanical properties of bulk tissues by measuring the propagation speed of shear waves (SW) induced in the tissue with an ultrasound transducer. The technique has been successfully validated in liver and breast (tumor) diagnostics and is potentially useful for the assessment of the stiffness of arteries. However, SW propagation in arteries is subjected to different wave phenomena potentially affecting the measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…The experimentally measured gauge length at 2 N load was adjusted to 47.87 mm at 0 N by taking into account the curve offset of -4.55 mm. The complete model length was 98.79 mm at 0 N. The thickness and width of the model were 4 mm and 74.2 mm (Shcherbakova et al, 2014). …”
Section: Mesh Geometry Boundary Conditions and Solution Methods To Mmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimentally measured gauge length at 2 N load was adjusted to 47.87 mm at 0 N by taking into account the curve offset of -4.55 mm. The complete model length was 98.79 mm at 0 N. The thickness and width of the model were 4 mm and 74.2 mm (Shcherbakova et al, 2014). …”
Section: Mesh Geometry Boundary Conditions and Solution Methods To Mmentioning
confidence: 99%
“…In a previous work (Shcherbakova et al, 2014), we demonstrated that SWE can detect stretch-induced stiffening of a slab of ex-vivo equine aortic tissue and pick up the cyclic variation in SWS related to the dynamic stretching of the material. Moreover, we showed SWE to be dependent on the orientation angle of the probe, and hypothesized that the SWS along the presumed fibre orientation exceeded the SWS across the fibres.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations